Design and development of integrated transplanter and weedermmachine for system of rice intesification (SRI) cultivation in Malaysia
System of rice intensifications (SRI) was practiced by community in Lembah Organik Lentang, Kampung Lentang since 2010. Throughout the years, the paddy plots began to grow in number. Since most of the SRI practices needed to be done manually especially planting the seedlings and using conventional tools to kill weeds and loaming the soil, the demand of machinery was inevitable. This is due to time consumed and numbers of manpower needed to carry out the task. For example, weeding process need to be done 4 times for one season. A new chassis that is able to support mechanical weeder and transplanter for SRI was developed. This project was designed to support SRI practices among Malaysian farmers. Product design specifications were gained from rice farmers situated at Kampung Lentang, Belantek, Kedah. Several concepts were generated and the best was choosen for further development and analysis. New chasiss was developed to replace the current agriculture tractor. The chassis was fit with small petrol engine and one main wheel. It was designed to pull SRI weeder and transplanter mechanism. The weeder mechanism was designed to loam three rows at once and able to be use for weeding process up to 40 days of age. Finite element analysis software was used to identify potential failures and subsequent rectification of the problem at the design stage. Some calculation was done to determine force and torque that may act on design. Steel was chosen as material to reduce fabrication cost. Stainless steel and aluminum were also initially considered as suitable material for the design but was not chosen due to the cost is high. For the rice transplanter, the transplanting mechanism uses linkage to drop rice seedlings on top of the soil. This fits the SRI practices for transplanting the young seedling. It is not just able to plant one seedling at one location but also plant the seedlings without removing it from nursery soil, thus, eliminate possibilities to injure the seedlings. Motion analysis was done to analyze the linkage movement. Finite element analysis also was done to determine maximum stress for each linkage part. Two of the designed products were built into prototype which are SRI Chassis and SRI Weeder and tested in actual working environment at paddy field. The field trial shows SRI Weeder was able to reduce manpower by 67%, working time by 42% and save 60% of overall operating cost